Mental Health Conditions and Unplanned Hospital Readmissions in Children. Issue 7 (1st July 2018) - Doupnik, Stephanie K.; Lawlor, John; Zima, Bonnie T.; Coker, Tumaini R.; Bardach, Naomi S.; Rehm, Kris P.; Gay, James C.; Hall, Matt; Berry, Jay G.
Abstract : OBJECTIVE: Mental health conditions (MHCs) are prevalent among hospitalized children and could influence the success of hospital discharge. We assessed the relationship between MHCs and 30‐day readmissions. METHODS: This retrospective, cross‐sectional study of the 2013 Nationwide Readmissions Database included 512, 997 hospitalizations of patients ages 3 to 21 years for the 10 medical and 10 procedure conditions with the highest number of 30‐day readmissions. MHCs were identified by using the International Classification of Diseases, 9th Revision‐Clinical Modification codes. We derived logistic regression models to measure the associations between MHC and 30‐day, all‐cause, unplanned readmissions, adjusting for demographic, clinical, and hospital characteristics. RESULTS: An MHC was present in 17.5% of medical and 13.1% of procedure index hospitalizations. Readmission rates were 17.0% and 6.2% for medical and procedure hospitalizations, respectively. In the multivariable analysis, compared with hospitalizations with no MHC, hospitalizations with MHCs had higher odds of readmission for medical admissions (adjusted odds ratio [AOR], 1.23; 95% confidence interval [CI], 1.19‐1.26] and procedure admissions (AOR, 1.24; 95% CI, 1.15‐1.33). Three types of MHCs were associated with higher odds of readmission for both medical and procedure hospitalizations: depression (medical AOR, 1.57; 95% CI, 1.49‐1.66; procedure AOR, 1.39; 95% CI, 1.17‐1.65), substance abuse (medical AOR, 1.24; 95% CI, 1.18‐1.30; procedure AOR, 1.26; 95% CI, 1.11‐1.43), and multiple MHCs (medical AOR, 1.43; 95% CI, 1.37‐1.50; procedure AOR, 1.26; 95% CI, 1.11‐1.44). CONCLUSIONS: MHCs are associated with a higher likelihood of hospital readmission in children admitted for medical conditions and procedures. Understanding the influence of MHCs on readmissions could guide strategic planning to reduce unplanned readmissions for children with cooccurring physical and mental health conditions.